2009
DOI: 10.1002/jbm.a.32568
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating tissue infiltration and angiogenesis in a tubular collagen scaffold

Abstract: Among different strategies to provide blood supply to tissue-engineered devices and implants, the use of arteriovenous loops and bundles has been proposed. The aim of this study was to compare the vascularization and healing processes that took place in a one-end closed tubular collagen-based scaffold at different implantation sites in mice. These conditions were in the presence or absence of heparin and/or bone marrow cells. By 30 days, very few cell infiltrations were observed in the dorsal subcutaneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…But the use of porous scaffolds as bone substitutes for large segmental bone defect treatment is usually hindered by the limited bone ingrowth, especially in the center region of grafts [19]. On the other hand, tubular design has been proposed in several studies as well, in order to mimic the tubular structure of long bone, with potential efficacy to facilitate bone tissue infiltration and vascularization [20], [21]. However, how the tubular scaffolds compared to porous ones as bone graft substitutes in terms of their osteoconductivity (bone tissue ingrowth) and vascularization during the defect treatment still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…But the use of porous scaffolds as bone substitutes for large segmental bone defect treatment is usually hindered by the limited bone ingrowth, especially in the center region of grafts [19]. On the other hand, tubular design has been proposed in several studies as well, in order to mimic the tubular structure of long bone, with potential efficacy to facilitate bone tissue infiltration and vascularization [20], [21]. However, how the tubular scaffolds compared to porous ones as bone graft substitutes in terms of their osteoconductivity (bone tissue ingrowth) and vascularization during the defect treatment still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of porous naturally derived scaffold or synthetic scaffold have demonstrated potential for therapeutic angiogenesis. A three‐dimensional scaffold acting as a cellular delivery vehicle can facilitate the exchange of oxygen and nutrients for cell growth, differentiation, and tissue functionality 12…”
Section: Introductionmentioning
confidence: 99%
“…A three-dimensional scaffold acting as a cellular delivery vehicle can facilitate the exchange of oxygen and nutrients for cell growth, differentiation, and tissue functionality. 12 Lyophilized type I collagen can stimulate wound healing by recruiting a number of different cell types (i.e., platelets and macrophages) and proteins (i.e., fibronectin). 13 Platelets and macrophages produce locally acting growth factors that in turn induce fibroblast migration and angiogenesis and increase matrix synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that a sheathed design was unfeasible due to limited vascularisation and the risk of infection due to avascular fluid build-up. In addition, tubular stents proposed in several earlier studies altered the natural loading pattern of the bone anatomical mismatch [69][70][71]. Accordingly, it is evident that stress shielding, osseointegration, and maladapted stress concentration are still a challenging problem for bone scaffolds.…”
Section: Discussionmentioning
confidence: 99%